1954
DOI: 10.1172/jci102926
|View full text |Cite
|
Sign up to set email alerts
|

Water Distribution in Normal Subjects and in Patients With Laënnec's Cirrhosis

Abstract: The development of ascites and edema in patients with Laennec's cirrhosis is believed by some to be due to a deranged hormonal balance which results in salt and water retention (1-5). The present investigation analyzes the components of total body water in 22 control subjects and 15 patients with Laennec's cirrhosis to ascertain the distribution of the retained salt and water. METHODSThe control subjects were patients on the surgical wards for minor procedures which influence water and electrolyte balance mini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
3
0

Year Published

1956
1956
1968
1968

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(4 citation statements)
references
References 10 publications
1
3
0
Order By: Relevance
“…The renal and hepatic disease groups, exhibited the theoretical change expected in individuals with straightforward extracellular fluid accumulation of moderate severity. Values of this order of magnitude for patients with cirrhosis of the liver have been reported by others (9).…”
Section: Discussionsupporting
confidence: 75%
“…The renal and hepatic disease groups, exhibited the theoretical change expected in individuals with straightforward extracellular fluid accumulation of moderate severity. Values of this order of magnitude for patients with cirrhosis of the liver have been reported by others (9).…”
Section: Discussionsupporting
confidence: 75%
“…Recently several other studies of this response have been reported (4)(5)(6)(7)(8) in both atrial and ventricular musculature of different species. In the experiments on rhythm.…”
Section: Solomon Garb Axd Mario P E N N A~ (Iyith the Technical Assismentioning
confidence: 91%
“…Some investigators have allowed 3 hours for D20 to equilibrate in certain pathologic states; thus they imply some delay in equilibration (6). Isotopes have facilitated this work; but no isotope is ideal since each has its own peculiar advantages and disadvantages.…”
mentioning
confidence: 99%
See 1 more Smart Citation